Nitrogen and carbon starvation regulate conidia and protoperithecia formation in Neurospora crassa grown on solid media - M. Ricci; D. Krappmann; V. E.A. Russo (Fungal Genetics Reports, 1991)
It is known that nitrogen and carbon limitation regulate conidiation in shaken liquid cultures (Guignard et al. 1984 Can. J. Microbiol. 30:1210-1215; Muller and Russo 1989 Fungal Genetics Newsletter 36:58-60), and that nitrogen starvation regulates protoperithecial formation in solid medium (Sommer et al. 1987 Planta 170:205-208).